Dielectric and ferroelectric properties of pb(Zr1/2Ti 1/2)O3-Pb(Ni1/3Nb2/3)O3 ceramics under perpendicular compressive stress - Unruan M. (2014)
The dielectric and ferroelectric properties of (1-x)Pb(Zr 1/2Ti1/2)O3-(x)Pb(Ni1/3Nb 2/3)O3 r (1-x)PZT-(x)PNN (x = 0.1-0.5) ceramics were measured under compressive stress applied perpendicular to an electric field direction. For the dielectric properties, the experimental results revealed that the superimposed perpendicular compression stress reduced the dielectric constant and the dielectric loss tangent of all compositions. The stress-induced changes the dissipation energy, the polarizations, however, depended significantly on ceramic compositions, but increases the coercive field of all the compositions. These results were interpreted through the non-180° ferroelastic domain switching processes, the stress clamping of domain walls, de-aging mechanism, and the stress induced enhance in switchable part of spontaneous polarization. Copyright © Taylor & Francis Group, LLC.